Sleep - A main pillar of recovery - Hödlmoser, K. (Journal of Biathlon Coaching, 2024)
There is no question that restful sleep is a prerequisite for mental and physical performance. In general, sleep is known to be an important factor in maintaining physical and psychological well-being. Sufficiently long and restful sleep is essential for optimal recovery after training or competition, but above all for preparing an athlete for a competition taking place the next day (Dement, 2005). Especially for athletes, many factors may negatively impact sleep and thereby might result in compromised athletic performance.